Morphometry, viability and germination of seeds of Benincasa hispida [(Thunb.) Cogn.] - Esptia-Camacho, Miguel; Villalba-Soto, Alisson; Aramédiz-Tatis, Hermes; Cardona-Ayala, Carlos (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
The objective of the study was to evaluate the morphometry, viability and germination of B. hispida seeds, at the Universidad de Córdoba, Colombia. Eight biometric characteristics were measured in a sample of seeds taken at random from a balanced compound originating from 50 fruits. The external and internal morphological description was made on a sample of 10 seeds. Seed viability was estimated by the tetrazolium test, using the combination of two staining times (2 and 3 hours) and three concentrations of (0.5, 1.0 and 1.5%), under a design completely randomized, with six treatments and four repetitions of 50 seeds. The germination test (PRUGER) was performed in a mesh house with four repetitions of 50 seeds to estimate eight physiological parameters of germination. The morpho-metric characteristics of thickness, length and width of seeds showed reduced phenotypic variation, compared with the weight, density and volume of a seed, with variation coefficients greater than 11.7%. The seed, ovoid and flattened, presents an embryo with its cotyledons wrapped in a protective membrane. The viability, determined with tetrazolium, was 89.5-96.5%, while the PRUGER was 100%, with no statistical differences between them (P≥0.05). The combination of 0.5% tetrazolium with 2 hours is sufficient to determine the viability of the seed. Germination elapsed from 6 to 19 days after sowing, with a germination speed index of 0.22, average daily germination of 5.26%, peak value of 5.33 and germination value of 28.